Correlation of the controlled attenuation parameter with indices of liver steatosis in overweight or obese individuals. Issue 3 (March 2015) - Ferraioli, Giovanna; Tinelli, Carmine; Lissandrin, Raffaella; Zicchetti, Mabel; Faliva, Milena; Perna, Simone; Perani, Guido; Alessandrino, Francesco; Calliada, Fabrizio; Rondanelli, Mariangela; Filice, Carlo
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to assess the clinical relevance of the controlled attenuation parameter (CAP) by analyzing the correlations between CAP and indirect indices of liver steatosis in obese or overweight individuals. Methods Consecutive participants were prospectively enrolled. BMI, waist circumference, hepatic steatosis index, fatty liver index, percent fat mass and regional fat masses as assessed by dual-energy X-ray absorptiometry (DXA), fat signal fraction as assessed by MRI, and CAP were obtained. Pearson's r coefficient was used to test the correlation between two study variables. Results A total of 88 individuals were studied. They included 31 men [age, 50.4 years (12.9 years); BMI, 30.7 kg/m2 (4.8 kg/m2)] and 57 women [age, 49.0 years (12.6 years); BMI, 31.4 kg/m2 (5.6 kg/m2)]. DXA, anthropometric parameters, and fatty liver index were moderately correlated with CAP in men. In women, there was a moderate correlation of CAP with the hepatic steatosis index and anthropometric parameters and only a slight or fair correlation of CAP with DXA parameters. CAP and fat signal fraction showed a good correlation (r=0.65 in men, P=0.002; r=0.68 in women, P=0.0009). Conclusion Measurement of CAP is a reliable method for noninvasive assessment of liver steatosis, showing a correlation with other indirect markers of central obesity and a good correlation with MRI results.